Preparation method and application of ferrocenyl photo-thermal nano material

Through the preparation method of ferrocene-based photothermal nanomaterials, click chemical reaction and amphiphilic polymers are used to solve the problem that existing photothermal nanoparticles are easily disintegrated in the internal environment, achieving higher photothermal conversion efficiency and Stability improves the effect of photothermal treatment.

CN119386180APending Publication Date: 2025-02-07GUANGZHOU JINYAN BIOMEDICAL RES INST CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411602013.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing organic photothermal nanoparticles are susceptible to factors such as temperature fluctuations and biological enzyme cleavage in complex internal environments, resulting in drug leakage and limiting the effectiveness of photothermal therapy.

Method used

Using the preparation method of ferrocene-based photothermal nanomaterials, nanoparticle cores with stronger hydrophobicity are prepared through click chemical reactions. Combined with amphiphilic polymers, the stability of nanoparticles is enhanced, and the high permeability long retention effect is achieved. The tumor site gathers.

Benefits of technology

It significantly improves the photothermal conversion efficiency of photosensitizers, enhances the stability of nanoparticles, reduces the risk of disintegration in the body, and improves the effect of photothermal therapy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386180A_ABST
    Figure CN119386180A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite nano materials, in particular to a preparation method and application of a ferrocenyl photo-thermal nano material, and the preparation method comprises the following steps: S1, preparing gamma-3-chloropropionyl-L-glutamate which is marked as CPLG; s2, preparing gamma-3-chloropropionyl-L-glutamic acid N-carboxylic acid anhydride, and recording the gamma-3-chloropropionyl-L-glutamic acid N-carboxylic acid anhydride as CPLG S3, preparing methoxy polyethylene glycol-b-poly (gamma-3-azidopropionyl-L-glutamic acid ester), and recording the methoxy polyethylene glycol-b-poly (gamma-3-azidopropionyl-L-glutamic acid ester) as mPEG-b-PAPLG; s4, preparing mPEG-block-poly (gamma-3-ferrocene propionyl-L-glutamic acid ester), and recording the mPEG-block-poly (gamma-3-ferrocene propionyl-L-glutamic acid ester) as MPF ( S5, preparing the ferrocenyl photo-thermal nano material; the prepared ferrocene-based photo-thermal nano material is used for photo-thermal therapy of tumors, an amphiphilic polymer and acetylene ferrocene are used for carrying out a click chemical reaction, the nano material has a nano particle core with higher hydrophobicity, leakage of an organic photosensitizer in the nano material can be effectively prevented, the nano material can cope with a complex in-vivo environment, and the photo-thermal therapy effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite nanomaterials, in particular to a preparation method and application of a ferrocene-based photothermal nanomaterial. Background Art

[0002] Photothermal therapy, with its significantly low side effects and excellent therapeutic effects, is expected to become another promising clinical tumor treatment method after surgery, chemotherapy, and radiotherapy.

[0003] Photothermal therapy is achieved by introducing photosensitizers into the body, such as organic photothermal converters IR780, IR808, and ICG, and then using near-infrared light applied in vitro for precise irradiation. During this process, the temperature of the tumor site rises sharply through photothermal conversion, thereby effectively triggering the anti-tumor mechanism and exerting an anti-tumor effect.

[0004] At present, the main challenge and innovation focus in the field of photothermal therapy is to develop photosensitizers with higher photothermal conversion efficiency. Although traditional organic photosensitizers have shown certain potential, they are limited by their relatively poor water solubility and easy metabolism in the body. When used alone, the photothermal conversion efficiency is relatively limited. In the existing technology, in order to overcome this bottleneck of traditional organic photosensitizers, polymer nanotechnology is used to encapsulate photosensitizers in nanoparticles to make organic photothermal nanoparticles, which can accumulate more effectively in the tumor area and significantly improve the tumor treatment effect.

[0005] However, the organic photothermal nanoparticles in the prior art are easily affected by temperature fluctuations, enzyme cleavage and other factors in the complex in vivo environment, causing disintegration, leading to drug leakage, thereby restricting the ultimate effect of photothermal therapy;

[0006] Therefore, enhancing the stability of organic photothermal nanoparticles has become the key to promoting the efficient delivery and release of organic photosensitizers in vivo. Summary of the invention

[0007] In order to improve the stability of organic photothermal nanoparticles and enhance the effect of photothermal therapy, the present application provides a preparation method and application of ferrocene-based photothermal nanomaterials.

[0008] The preparation method and application of a ferrocene-based photothermal nanomaterial provided by the present invention adopt the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a ferrocene-based photothermal nanomaterial, using the following technical solution:

[0010] A method for preparing a ferrocene-based photothermal nanomaterial, characterized in that it comprises the following steps:

[0011] S1. Preparation of CPLG substance: L-glutamic acid, anhydrous ether and 3-chloropropanol are mixed to form a first mixed solution; after the first mixed solution is cooled to about 0°C, sulfuric acid is added to the first mixed solution, and stirred at room temperature for 48 hours to form a second mixed solution; the second mixed solution is neutralized with pyridine, and placed in a 4°C environment for 18 hours to form a third mixed solution; isopropanol / water mixed solution is added to the third mixed solution to form a fourth mixed solution; the fourth mixed solution is heated to 85°C to recrystallize the fourth mixed solution, and a white precipitate can be obtained after filtering, which is γ-3-chloropropionyl-L-glutamate, and the substance is recorded as CPLG;

[0012] S2. Preparation of CPLG-NCA substance: CPLG, triphosgene and tetrahydrofuran in S1 are mixed, stirred in an oil bath at 50°C, and tetrahydrofuran is removed under vacuum to obtain an oily liquid; the oily liquid is dissolved in 100 ml of ethyl acetate at 4°C, and then washed three times with 100 ml of a 0.5% sodium bicarbonate aqueous solution precooled at 4°C to obtain an organic phase; the organic phase is dried over anhydrous magnesium sulfate at 0°C for 3 hours, impurities are removed by filtration, and the organic solution is removed by distillation under reduced pressure to obtain γ-3-chloropropionyl-L-glutamic acid N-carboxylic anhydride, which is recorded as CPLG-NCA;

[0013] S3. Preparation of mPEG-b-PAPLG material: dissolve the CPLG-NCA in S2 in 10 ml of anhydrous dimethylformamide to a final concentration of 0.25 g / ml, stir at room temperature for 72 hours, then dialyze against deionized water for 48 hours, collect the dialyzed product and lyophilize it to obtain methoxy polyethylene glycol-b-poly in the form of white powder, dissolve methoxy polyethylene glycol-b-poly (γ-3-chloropropionyl-L-glutamate) and sodium azide in dimethyl sulfoxide, stir at 60°C for 48 hours, then dialyze against deionized water for 48 hours to remove inorganic salts and organic solutions, collect the dialyzed product and lyophilize it to obtain methoxy polyethylene glycol-b-poly (γ-3-azidopropionyl-L-glutamate), which is recorded as mPEG-b-PAPLG;

[0014] S4. Preparation of MPF substance: mPEG-b-PAPLG and ethynylferrocene prepared in S3 are added to dimethyl sulfoxide to obtain a first mixture, copper sulfate pentahydrate and sodium ascorbate are added to the first mixture under a nitrogen environment, and the mixture is stirred in an oil bath at 50° C. for 24 hours, followed by dialysis and freeze-drying to obtain a yellow solid, i.e., mPEG-b-poly(γ-3-ferrocenepropionyl-L-glutamate), which is recorded as MPF;

[0015] S5. Preparation of ferrocene-based photothermal nanomaterials: The MPF in S4 is uniformly mixed with the photosensitizer, dissolved in dimethyl sulfoxide, and added into a centrifuge tube containing distilled water to form a second mixture. The second mixture is dialyzed in the dark, and the solution is collected after 48 hours to obtain a ferrocene-based photothermal nanoparticle solution.

[0016] Preferably, the first mixed solution in S1 is prepared by mixing 14.71 g, 100 mmol of L-glutamic acid, 60 ml of anhydrous ether and 30 ml of 3-chloropropanol.

[0017] Preferably, the isopropanol / water mixture in S1 is prepared by mixing isopropanol and water in a volume ratio of V 异丙醇 :V 水 =85:15.

[0018] Preferably, the amount of pyridine added in S1 is 4 times the amount of sulfuric acid added, wherein the amount of sulfuric acid added is 5 ml and the amount of pyridine added is 20 ml.

[0019] Preferably, in S2, 4 g, 17.8 mmol of CPLG, 2 g, 6.73 mmol of triphosgene and 50 ml of tetrahydrofuran are mixed in a flame-dried round-bottom flask.

[0020] Preferably, in S3, 0.25 g, 0.05 mmol of methoxypolyethylene glycolamine is used as an initiator, and CPLG-NCA is dissolved in 10 ml of dimethylformamide under flowing nitrogen to a final concentration of 0.25 g / ml.

[0021] Preferably, in S5, MPF and the photosensitizer are uniformly mixed in a weight ratio of 10:1, dissolved in 1 mL of dimethyl sulfoxide, and slowly added into a centrifuge tube containing 5 mL of distilled water.

[0022] Preferably, in S5, the second mixture is transferred to a dialysis bag with a molecular weight cutoff of 3500Da, placed in a beaker filled with distilled water for light-proof dialysis for 48 hours, and the distilled water in the beaker is replaced every 8 hours.

[0023] Preferably, the photosensitizer described in S5 is one of IR780, IR800, and IR808.

[0024] In a second aspect, the present invention provides an application of a ferrocene-based photothermal nanomaterial, wherein the ferrocene-based photothermal nanomaterial prepared by the above-mentioned preparation method is used for photothermal therapy of tumors.

[0025] The beneficial effects of the present invention are:

[0026] The photothermal nanoparticles prepared by the present invention can effectively improve the photothermal conversion efficiency of the photosensitizer. First, since the nanoparticles have a hydrophilic shell and a hydrophobic core, they can wrap the hydrophobic photosensitizer in their core, increase their dispersibility in aqueous solution, and then increase the surface area receiving light, thereby increasing the photothermal conversion efficiency; secondly, the polymer nanoparticles wrap the photosensitizer inside to form an aggregation-induced fluorescence quenching effect, so that the energy of the light is transferred to the direction of heat energy, and exert a more powerful photothermal conversion effect.

[0027] The present invention utilizes an amphiphilic polymer to carry out a click chemistry reaction with acetylene ferrocene to prepare an MPF ​​polymer having a more hydrophobic nanoparticle core, which can effectively prevent the leakage of an organic photosensitizer inside the nanoparticle, improve the stability of the ferrocene-based photothermal nanomaterial, cope with complex in vivo environments, and reduce the risk of disintegration of the ferrocene-based photothermal nanomaterial in vivo due to various factors such as temperature fluctuations and enzyme cleavage.

[0028] The photothermal nanoparticles prepared by the present invention can better aggregate at the tumor site through the high permeability and long retention effect at the nanoscale, increase the content of the photosensitizer in the tumor, and improve the photothermal treatment effect.

[0029] The photothermal nanoparticles prepared by the present invention have stronger internal hydrophobicity and higher compactness due to the presence of ferrocene, so the aggregation-induced fluorescence quenching effect is stronger and the photothermal conversion effect is better.

[0030] The ferrocene in the photothermal nanoparticles prepared by the present invention contains divalent iron ions, which can induce ferroptosis in tumor cells and increase the anti-tumor effect.

[0031] The photothermal nanoparticles prepared by the present invention generate a large amount of active oxygen, such as hydrogen peroxide, during the photothermal treatment process. The hydrogen peroxide can react with divalent iron ions to produce more toxic hydroxyl radicals, thereby exerting a better anti-tumor effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a light-to-heat conversion performance analysis diagram in this application;

[0033] Figure 2 is a transmission electron microscope image in Example 2 of the present application;

[0034] Figure 3 It is a tumor cell inhibition performance analysis diagram in this application;

[0035] Figure 4 It is a process flow chart of an embodiment of the present application. DETAILED DESCRIPTION

[0036] This section will describe in detail the specific embodiments of the present application. The preferred embodiments of the present application are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that each technical feature and the overall technical solution of the present application can be understood intuitively and vividly, but it cannot be understood as a limitation on the scope of protection of the present application.

[0037] In the description of this application, if there is a description of orientation, for example, the orientation or position relationship indicated by "upper", "lower", "front", "back", "left", "right", etc. is based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing this application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this application. When a feature is referred to as "set", "fixed", or "connected" to another feature, it can be directly set, fixed, or connected to the other feature, or it can be indirectly set, fixed, or connected to the other feature.

[0038] In the description of this application, if "several" is involved, it means one or more, if "multiple" is involved, it means more than two, if "greater than", "less than", "exceed", they should be understood as not including the number, if "above", "below", "within" are involved, they should be understood as including the number. If "first" or "second" is involved, it should be understood as being used to distinguish technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0039] In addition, unless otherwise defined, the technical terms and scientific terms used in this application are the same as those generally understood by those skilled in the art. The terms used in this application are only for describing specific embodiments, not for limiting this application. It should be understood that when used in this specification and the appended claims, the terms "include" and "comprise" indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.

[0040] Embodiment 1: A method for preparing a ferrocene-based nanomaterial, comprising the following steps:

[0041] S1. 14.71 g, 100 mmol of L-glutamic acid, 60 ml of anhydrous ether and 30 ml, 317 mmol of 3-chloropropanol were added to a 250 ml round-bottom flask for mixing to prepare a first mixed solution. After the first mixed solution was cooled to about 0° C., 5 ml of sulfuric acid was added to the first mixed solution using a syringe, and the mixture was stirred at room temperature for 48 hours to form a second mixed solution. The second mixed solution was then neutralized with 20 ml of pyridine, and the second mixed solution was placed in a refrigerator at 4° C. for 18 hours to form a third mixed solution. Isopropanol / water (V 2 ) was added to the third mixed solution. 异丙醇 :V 水 =85:15) mixed solution to form a fourth mixed solution, the fourth mixed solution was filtered and recrystallized at 85°C to obtain a white precipitate with a yield of 35%, and 7.8 g of γ-3-chloropropionyl-L-glutamate was obtained, which was recorded as: CPLG;

[0042] S2. 4 g, 17.8 mmol of CPLG in S1, 2 g, 6.73 mmol of triphosgene and 50 ml of tetrahydrofuran were mixed in a flame-dried round-bottom flask, stirred in a 50° C. oil bath, and tetrahydrofuran was removed under vacuum to obtain an oily liquid, which was dissolved in 100 ml of ethyl acetate cooled at 4° C., and then the mixture was washed three times with 100 ml of 0.5% sodium bicarbonate (NaHCO3) aqueous solution cooled at 4° C., and the organic phase was dried over anhydrous magnesium sulfate (MgSO4) at 0° C. for 3 hours, and impurities were removed by filtration. The organic solution was removed by distillation under reduced pressure to obtain about 2.5 g of γ-3-chloropropionyl-L-glutamic acid N-carboxylic anhydride, which was recorded as CPLG-NCA;

[0043] S3. 2.5 g of CPLG-NCA in S2 was dissolved in 10 ml of anhydrous dimethylformamide (DMF) to a final concentration of 0.25 g / ml. 0.25 g, 0.05 mmol of methoxypolyethylene glycolamine was used as a macro-initiator and dissolved in 10 ml of anhydrous dimethylformamide (DMF) under flowing nitrogen. A measured volume of CPLG-NCA / DMF solution (1 ml, 0.25 g, 1 mmol) was added to the solution using a syringe and stirred at room temperature for 72 hours. After the reaction, the mixture was transferred to a dialysis tube with a molecular cutoff of 8–14 kDa and dialyzed with deionized water for 2 days, i.e., 48 hours. The dialyzed product was collected and lyophilized to obtain 0 .4g polymer, the recovery rate is 87.5%, the obtained methoxy polyethylene glycol-b-poly (γ-3-chloropropionyl-L-glutamate; 0.4g, about 0.75mmol chlorine group) and sodium azide (0.3g, 4.6mmol) are dissolved in 15ml dimethyl sulfoxide (DMSO), and stirred at 60°C for 48 hours, the mixture is transferred to a dialysis tube with a molecular cutoff of 8-14kDa, and dialyzed with deionized water for 2 days, i.e. 48 hours, to remove inorganic salts and organic solutions, the dialyzed product is collected and lyophilized to produce about 0.37g methoxy polyethylene glycol-b-poly (γ-3-azidopropionyl-L-glutamate), recorded as mPEGb-PAPLG;

[0044] S4. Post-polymerization functionalization was performed to couple ferrocene to the polypeptide. mPEG-b-PAPLG (100 mg, about 0.20 mmol azide group) and ethynylferrocene (85 mg, 0.40 mmol) in S3 were added to 10 ml of dimethyl sulfoxide (DMSO) to obtain a first mixture, and then 15 mg, 0.06 mmol of copper sulfate pentahydrate (CuSO4·5H2O) and 23 mg, 0.12 mmol of sodium ascorbate (NaAsc) were introduced into the first mixture under nitrogen. The first mixture was stirred in a 50°C oil bath for 24 h, followed by dialysis and freeze-drying, with a yield of 94%, to obtain 133 mg of a yellow solid, namely mPEG-block-poly (γ-3-ferrocenylpropionyl-L-glutamate), denoted as MPF.

[0045] Example 2: A method for preparing a ferrocene-based nanomaterial loaded with IR780, comprising the following steps:

[0046] A1. 10 mg of MPF in Example 1 and 1 mg of IR780 were dissolved in 1 mL of dimethyl sulfoxide (DMSO) and slowly added to a centrifuge tube containing 5 mL of distilled water to form a second mixture;

[0047] A2. The second mixture in A1 was transferred to a dialysis bag with a molecular weight cutoff of 3500Da, and placed in a beaker filled with distilled water for dialysis. The distilled water in the beaker was replaced every 8 hours. The whole process was protected from light. After 48 hours, the desired nanomaterial was obtained, represented by MPF@IR780. The nanomaterial was transferred to a 15ml centrifuge tube and kept in the dark at room temperature for later use.

[0048] Example 3: A method for preparing a ferrocene-based nanomaterial loaded with IR808, comprising the following steps:

[0049] A1. 10 mg of MPF in Example 1 and 1 mg of IR808 were dissolved in 1 mL of dimethyl sulfoxide (DMSO) and slowly added to a centrifuge tube containing 5 mL of distilled water to form a second mixture;

[0050] A2. The second mixture in A1 was transferred to a dialysis bag with a molecular weight cutoff of 3500Da, and placed in a beaker filled with distilled water for dialysis. The distilled water in the beaker was replaced every 8 hours. The whole process was protected from light. After 48 hours, the desired nanomaterial was obtained, represented by MPF@IR808. The nanomaterial was transferred to a 15ml centrifuge tube and kept in the dark at room temperature for later use.

[0051] Example 4: A method for preparing an ICG-loaded ferrocene-based nanomaterial, comprising the following steps:

[0052] A1. 10 mg of MPF in Example 1 and 1 mg of ICG were dissolved in 1 mL of dimethyl sulfoxide (DMSO) and slowly added to a centrifuge tube containing 5 mL of distilled water to form a second mixture;

[0053] A2. The second mixture in A1 was transferred to a dialysis bag with a molecular weight cutoff of 3500Da, and placed in a beaker filled with distilled water for dialysis. The distilled water in the beaker was replaced every 8 hours. The whole process was protected from light. After 48 hours, the desired nanomaterial was obtained, represented by MPF@ICG. The nanomaterial was transferred to a 15ml centrifuge tube and kept in the dark at room temperature for later use.

[0054] Comparative Example 1: A method for preparing a polymer nanomaterial, comprising the following steps:

[0055] S1. L-glutamic acid (14.71 g, 100 mmol), 60 ml of anhydrous ether and 3-chloropropanol (30 ml, 317 mmol) were added to a 250 ml round-bottom flask, and the mixture was cooled to about 0°C, 5 ml of sulfuric acid was added to the solution using a syringe, and stirred at room temperature for 48 hours. Then, the solution was neutralized with 20 ml of pyridine, and the mixture was placed in a refrigerator at 4°C for 18 hours, and then heated at 85°C in isopropanol / water (V 异丙醇 :V水 =85:15) was filtered and recrystallized to obtain a white precipitate with a yield of 35%, and 7.8 g of γ-3-chloropropionyl-L-glutamate was obtained, which was recorded as CPLG;

[0056] S2. CPLG (4 g, 17.8 mmol) in S1, triphosgene (2 g, 6.73 mmol) and 50 ml tetrahydrofuran were mixed in a flame-dried round-bottom flask, stirred in a 50° C. oil bath, and tetrahydrofuran was removed under vacuum to obtain an oily liquid. The oily liquid was dissolved in 100 ml of ethyl acetate cooled at 4° C., and then the mixture was washed three times with 100 ml of 0.5% sodium bicarbonate (NaHCO3) aqueous solution cooled at 4° C. The organic phase was dried over anhydrous magnesium sulfate (MgSO4) at 0° C. for 3 hours, impurities were removed by filtration, and the organic solution was removed by reduced pressure distillation to obtain about 2.5 g of γ-3-chloropropionyl-L-glutamic acid N-carboxylic anhydride, denoted as: CPLG-NCA;

[0057] 2.5 g of CPLG-NCA in S3.S2 was dissolved in 10 ml of anhydrous dimethylformamide (DMF) to a final concentration of 0.25 g / ml, and methoxypolyethylene glycolamine (0.25 g, 0.05 mmol) was used as a macro-initiator and dissolved in 10 ml of anhydrous DMF under flowing nitrogen. A measured volume of CPLG-NCA / DMF solution (1 ml, 0.25 g, 1 mmol) was added to the solution using a syringe and stirred at room temperature for 72 hours. After the reaction, the mixture was transferred to a dialysis tube (molecular cutoff of 8–14 kDa) and dialyzed with deionized water for 2 days. The dialyzed product was collected and freeze-dried to obtain the polymer in the form of a white powder with a recovery rate of 87.5% (0.4 g). The obtained methoxypolyethylene glycol-b-poly(γ-3-chloropropionyl-L-glutamate; 0.4 g, about 0.75 mmol chloro group) and sodium azide (0.3 g, 4.6 mmol) were dissolved in dimethyl sulfoxide (DMSO) and stirred at 60°C for 48 hours. The mixture was transferred to a dialysis tube (molecular cutoff of 8-14 kDa) and dialyzed with deionized water for 2 days to remove inorganic salts and organic solutions. The dialyzed product was collected and lyophilized to produce about 0.37 g methoxypolyethylene glycol-b-poly(γ-3-azidopropionyl-L-glutamate), recorded as MP.

[0058] Comparative Example 2: A method for preparing a polymer nanomaterial loaded with IR780, comprising the following steps:

[0059] A1. Take 10 mg of MP in Comparative Example 1 and 1 mg of IR780, dissolved in 1 mL of dimethyl sulfoxide (DMSO), and slowly added to a centrifuge tube containing 5 mL of distilled water to form a second mixture;

[0060] A2. The second mixture in A1 was transferred to a dialysis bag with a molecular weight cutoff of 3500Da, and placed in a beaker filled with distilled water for dialysis. The distilled water in the beaker was replaced every 8 hours. The whole process was protected from light. After 48 hours, the desired nanomaterial was obtained, represented by MP@IR780. The nanomaterial was transferred to a 15ml centrifuge tube and kept in the dark at room temperature for later use.

[0061] Comparative Example 3: A method for preparing a polymer nanomaterial loaded with IR808, comprising the following steps:

[0062] A1. Take 10 mg of MP in Comparative Example 1, and 1 mg of IR808, dissolved in 1 mL of dimethyl sulfoxide (DMSO), and slowly added to a centrifuge tube containing 5 mL of distilled water to form a second mixture;

[0063] A2. The second mixture in A1 was transferred to a dialysis bag with a molecular weight cutoff of 3500Da, and placed in a beaker filled with distilled water for dialysis. The distilled water in the beaker was replaced every 8 hours. The whole process was protected from light. After 48 hours, the desired nanomaterial was obtained, represented by MP@IR808. The nanomaterial was transferred to a 15ml centrifuge tube and kept in the dark at room temperature for later use.

[0064] Comparative Example 4: A method for preparing an ICG-loaded polymer nanomaterial, comprising the following steps:

[0065] A1. Take 10 mg of MP in Example 1 and 1 mg of ICG, dissolve them in 1 mL of dimethyl sulfoxide (DMSO), and slowly add them to a centrifuge tube containing 5 mL of distilled water to form a second mixture;

[0066] A2. The second mixture in A1 was transferred to a dialysis bag with a molecular weight cutoff of 3500Da, and placed in a beaker filled with distilled water for dialysis. The distilled water in the beaker was replaced every 8 hours. The whole process was protected from light. After 48 hours, the desired nanomaterial was obtained, represented by MP@ICG. The nanomaterial was transferred to a 15ml centrifuge tube and kept in the dark at room temperature for later use.

[0067] Analysis of photothermal conversion performance of ferrocene polymer nanoparticles:

[0068] The photothermal conversion performance of MPF loaded with different photosensitizers in Examples 2-4 and MP loaded with different photosensitizers in Comparative Examples 2-4 were tested.

[0069] The specific method is as follows: After loading different photosensitizers onto polymer nanoparticles (MPF) with ferrocene, the fluorescence quenching and photothermal conversion enhancement effects of MPF encapsulated photosensitizers were compared with the same concentration of free photosensitizers and polymer nanoparticles (MP) without ferrocene under near-infrared light (808nm) illumination through fluorescence imaging and thermal imaging.

[0070] Reference Figure 1 The results show that the ferrocene-based polymer-loaded photosensitizer material of the present invention has a very high photothermal conversion efficiency and is a good photothermal conversion nanomaterial.

[0071] TEM analysis of ferrocenyl polymer-supported IR780 materials:

[0072] The ferrocenyl polymer-loaded IR780 material obtained in Example 2 was subjected to microscopic examination using a transmission electron microscope (TEM). The results are as follows: Figure 2 As shown, the hydrophilic shell and the hydrophobic core can wrap the hydrophobic photosensitizer in its core, increase its dispersibility in the aqueous solution, and then increase the surface area receiving light and increase the photothermal conversion efficiency.

[0073] Analysis of tumor cell inhibition performance:

[0074] Prostate cancer DU145 cells were seeded in a 24-well plate at a density of 5×105 cells / well. After 24 hours, complete culture medium containing MPF, IR780, and MPF@IR780 (IR780 concentration was 2 μg / mL) was added. After another 4 hours, the cells were irradiated with near-infrared light (laser power density: 1.4 W / cm2, irradiation time: 3 min). After another 12 hours, live and dead cells were detected under a fluorescence microscope using an AM / PI kit. The results are shown in Figure 2. Figure 3 shown.

[0075] The results showed that ferrocene-based polymer-loaded IR780 material can effectively inhibit the viability of prostate cancer DU145 cells and is an effective tumor suppressor.

[0076] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a ferrocene-based photothermal nanomaterial, characterized in that: The following steps are involved: S1. Preparation of CPLG substance: L-glutamic acid, anhydrous ether and 3-chloropropanol are mixed to form a first mixed solution; after the first mixed solution is cooled to about 0°C, sulfuric acid is added to the first mixed solution, and stirred at room temperature for 48 hours to form a second mixed solution; the second mixed solution is neutralized with pyridine, and placed in a 4°C environment for 18 hours to form a third mixed solution; isopropanol / water mixed solution is added to the third mixed solution to form a fourth mixed solution; the fourth mixed solution is heated to 85°C to recrystallize the fourth mixed solution, and a white precipitate can be obtained after filtering, which is γ-3-chloropropionyl-L-glutamate, and the substance is recorded as CPLG; S2. Preparation of CPLG-NCA substance: CPLG, triphosgene and tetrahydrofuran in S1 are mixed, stirred in an oil bath at 50°C, and tetrahydrofuran is removed under vacuum to obtain an oily liquid; the oily liquid is dissolved in 100 ml of ethyl acetate at 4°C, and then washed three times with 100 ml of a 0.5% sodium bicarbonate aqueous solution precooled at 4°C to obtain an organic phase; the organic phase is dried over anhydrous magnesium sulfate at 0°C for 3 hours, impurities are removed by filtration, and the organic solution is removed by distillation under reduced pressure to obtain γ-3-chloropropionyl-L-glutamic acid N-carboxylic anhydride, which is recorded as CPLG-NCA; S3. Preparation of mPEG-b-PAPLG material: dissolve the CPLG-NCA in S2 in 10 ml of anhydrous dimethylformamide to a final concentration of 0.25 g / ml, stir at room temperature for 72 hours, then dialyze against deionized water for 48 hours, collect the dialyzed product and lyophilize it to obtain methoxy polyethylene glycol-b-poly in the form of white powder, dissolve methoxy polyethylene glycol-b-poly (γ-3-chloropropionyl-L-glutamate) and sodium azide in dimethyl sulfoxide, stir at 60°C for 48 hours, then dialyze against deionized water for 48 hours to remove inorganic salts and organic solutions, collect the dialyzed product and lyophilize it to obtain methoxy polyethylene glycol-b-poly (γ-3-azidopropionyl-L-glutamate), which is recorded as mPEG-b-PAPLG; S4. Preparation of MPF substance: mPEG-b-PAPLG and ethynylferrocene prepared in S3 are added to dimethyl sulfoxide to obtain a first mixture, copper sulfate pentahydrate and sodium ascorbate are added to the first mixture under a nitrogen environment, and the mixture is stirred in an oil bath at 50° C. for 24 hours, followed by dialysis and freeze-drying to obtain a yellow solid, namely mPEG-block-poly(γ-3-ferrocenepropionyl-L-glutamate), which is recorded as MPF; S5. Preparation of ferrocene-based photothermal nanomaterials: The MPF in S4 is uniformly mixed with the photosensitizer, dissolved in dimethyl sulfoxide, and added into a centrifuge tube containing distilled water to form a second mixture. The second mixture is dialyzed in the dark, and the solution is collected after 48 hours to obtain a ferrocene-based photothermal nanoparticle solution.

2. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1, characterized in that: The first mixed solution in S1 is prepared by mixing 14.71 g, 100 mmol, of L-glutamic acid, 60 ml of anhydrous ether and 30 ml of 3-chloropropanol.

3. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1 or 2, characterized in that: The isopropanol / water mixture in S1 is prepared by mixing isopropanol and water in a volume ratio of V 异丙醇 :V 水 =85:

15.

4. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1, 2 or 3, characterized in that: The amount of pyridine added in S1 is 4 times the amount of sulfuric acid added, wherein the amount of sulfuric acid added is 5 ml and the amount of pyridine added is 20 ml.

5. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1, characterized in that: In S2, 4 g, 17.8 mmol, of CPLG, 2 g, 6.73 mmol, of triphosgene, and 50 ml of tetrahydrofuran were mixed in a flame-dried round-bottom flask.

6. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1, characterized in that: In S3, 0.25 g, 0.05 mmol of methoxypolyethylene glycolamine was used as an initiator, and CPLG-NCA was dissolved in 10 ml of dimethylformamide under flowing nitrogen to a final concentration of 0.25 g / ml.

7. The preparation method and application of a ferrocene-based photothermal nanomaterial according to claim 1, characterized in that: In S5, MPF and photosensitizer were mixed evenly at a weight ratio of 10:1, dissolved in 1 mL of dimethyl sulfoxide, and slowly added into a centrifuge tube containing 5 mL of distilled water.

8. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1 or 7, characterized in that: In S5, the second mixture is transferred to a dialysis bag with a molecular weight cutoff of 3500 Da, and placed in a beaker filled with distilled water for 48 hours in the dark, and the distilled water in the beaker is replaced every 8 hours.

9. The method for preparing a ferrocene-based photothermal nanomaterial according to claim 1, 7 or 8, characterized in that: The photosensitizer described in S5 is one of IR780, IR800, and IR808.

10. An application of a ferrocene-based photothermal nanomaterial, characterized in that: The ferrocene-based photothermal nanomaterial prepared according to any one of claims 1 to 9 is used for photothermal therapy of tumors.